The healing Goddess Gula : towards an understanding of ancient Babylonian medicine - Bock, Barbara. (Culture and History of the Ancient Near East, 2013)
Providing a comprehensive examination of the traits and areas of authority Ancient Babylonians attributed to their healing goddess, this book draws on a wide range of Sumero-Akkadian cuneiform sources, including god lists, literary compositions, lexical lists, prognostic texts, incantations, and prescriptions. Analysing the use of selected metaphors associated with the goddess, a new perspective is offered on the explanation for disease as well as the motivation for particular treatments. Special chapters deal with the cuneiform handbook on prognosis and diagnosis of diseases, medical incantations appealing to the healing goddess, and the medicinal plants attributed to her. For the first time a body of evidence for the use of simple drugs is brought together, elaborating on specific plant profiles. The result is a volume that challenges many long-held assumptions concerning the specialized cuneiform medical literature and takes a fresh look on the nature of Ancient Babylonian healing.